Humanized single domain antibodies neutralize SARS-CoV-2 by targeting the spike receptor binding domain - Xiaojing Chi (Nature Portfolio, 2020)
Here, using a humanized phage display library with recombinant SARS- CoV-2 receptor binding domain (RBD) proteins, the authors identify a number of single domain antibodies (sdAbs) that neutralize SARS-CoV-2 in vitro by inhibiting the interaction of the RDB with the host entry receptor ACE2.